Cyclic behavior of AZ31B Mg: Experiments and non-isothermal forming simulations. (December 2015) - Lee, Chung An; Lee, Myoung-Gyu; Seo, Oh Suk; Nguyen, Ngoc-Trung; Kim, Ji Hoon; Kim, Heon Young
Abstract: Magnesium (Mg) alloys have unique room temperature mechanical properties such as yielding asymmetry, anisotropy, and unusual hardening response under strain path change. Mg alloy sheets often represent inferior formability at room temperature due to their limited active slip systems induced from specific microstructure and texture. This low formability is known to be mitigated as temperature increases, which is the result of active non-basal slip systems. Considering these unique properties, Mg alloy sheets has been often formed at 200 °C or higher. For optimizing the forming process using Mg alloy sheets, accurate constitutive models describing the unique behavior of the materials under non-proportional loading and non-isothermal temperature conditions are vital. In this paper, the mechanical behavior of AZ31B Mg alloy sheets under in-plane tension–compression (or compression-tension) cyclic loading was experimentally measured for various pre-strains and temperatures. Then, a practical hardening model modified from existing advanced hardening law was applied to calculate the stress–strain responses and formability in the cross shape die forming under non-isothermal condition.